A Study of Chip Formation on Turning with Minimum Quantity Lubrication Method (MQL) - Qoryah, Rika Dwi Hidayatul; Azizi, Agil Widhy; Darsin, Mahros (Politeknik Elektronika Negeri Surabaya (PENS), 2020)
The cutting fluid is one of the essential factors in machining to increase machinability. The issuance of ISO 14000 about reducing the use of cutting fluid for its danger for operator and environment has encouraged many researchers to find ways to minimize its use. The Minimum Quantity Lubrication (MQL) is an answer to it. To further reduce the use of cutting fluid, a device that complies with MQL criteria for controlling the spray based on the tool temperature has successfully designed. This paper is discussing the effect of applying this device to the chips formation. The experiments were on turning of AISI 4340 using carbide tools. The Taguchi method L9 used to design the experiments. The variations made on the method of applying the cutting fluid, depth of cut, and cutting fluid composition. The chips formation was calculated based on the value of the degree of serration. Analysis of the S/N ratio, followed by ANOVA, revealed that the cutting fluids application method is the least factor affecting the chips formation. In contrast, the depth of cut influences the chips formation by 75 per cent more. The highest degree of serration achieved when applying the combination of depth of cut of 1.8 mm, the composition of 5:5, and flood method of applying cutting fluid.